How referential uncertainty is modulated by conjunctions: ERP evidence from advanced Chinese–English L2 learners and English L1 speakers. (April 2019) - Xu, Xiaodong; Pan, Meizhu; Dai, Haoyun; Zhang, Hui; Lu, Yiyi
Conjunctions play a crucial role in the construction of a coherent mental representation by signaling coherence relations between clauses, especially for second language users. By using event-related potentials (ERPs), this study aimed to investigate how different conjunctions ( so, and, although, or a full stop ) affect the interpretation of a following ambiguous pronoun for both native and non-native speakers, in sentences such as Lily disappointed Nina, so she … . ERP results showed that relative to so, and, and full stop sentences, the pronoun in although clauses elicited a larger Nref (sustained negativity) response in both native (L1) readers and second language (L2) readers, irrespective of whether the verb in the first clause biased towards a particular noun phrase (NP) referent. Moreover, larger Nrefs to pronouns were seen in L2 than L1 readers when clauses were connected by so, although or a full stop . Additionally, larger Nref responses were evoked by pronouns in NP2- than NP1-biased conditions when the clauses were connected by the conjunction so or when sentences contained no overt conjunctions ( full stop ). These findings indicate that different conjunctions exert different modulating effects on resolving referential uncertainty/ambiguity. Relative to native speakers, non-native speakers are more likely to encounter referential uncertainty when the sentences are conjoined by conjunctions with more complex semantics.